2007 IEEE Conference on Computer Vision and Pattern Recognition 2007
DOI: 10.1109/cvpr.2007.383143
|View full text |Cite
|
Sign up to set email alerts
|

A Fast 3D Correspondence Method for Statistical Shape Modeling

Abstract: Accurately identifying corresponded landmarks from a population of shape instances is the major challenge in con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Medial-axis parameterizations of shape have also been used to construct nonlinear shape models and applied in a number of neurobiology studies [46,97]. Dalal, et al proposed a sliding landmark method which has been shown to compare favorably to the spherical harmonics methods [24,80]. Their method establishes correspondence by minimizing the bending energy of the thin-plate spline mapping between sample landmarks and a template.…”
Section: Computationally-derived Shape Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medial-axis parameterizations of shape have also been used to construct nonlinear shape models and applied in a number of neurobiology studies [46,97]. Dalal, et al proposed a sliding landmark method which has been shown to compare favorably to the spherical harmonics methods [24,80]. Their method establishes correspondence by minimizing the bending energy of the thin-plate spline mapping between sample landmarks and a template.…”
Section: Computationally-derived Shape Modelsmentioning
confidence: 99%
“…Correspondence-based computational models of shape in the literature rely on spherical parameterizations of shape and can therefore represent only manifold surfaces with spherical topologies. This limitation also precludes the analysis of many important open-boundary anatomical structures such as the diaphragm [24] or of localized regions of a structure, such as head of a bone. Another important consideration is that medical or biological shapes are typically derived from the interfaces between organs or tissue types and usually defined implicitly in the form of segmented volumes, rather than explicit parameterizations, triangulations, or surface point samples.…”
Section: Shape Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to this paper is the 3D landmark-sliding method SLIDE [10] that can be used to correspond both opensurface and closed-surface shape instances. In this method, each target shape instance is first aligned with a given template shape.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this alignment, an initial estimate of the corresponding landmarks is established and a landmarksliding framework is developed to refine the initial estimates of corresponding landmarks. Compared to MDL and SPHARM, this method requires less CPU time and usually leads to a PDM with better compactness, generality and specificity characteristics [10]. However, this method does not guarantee that the landmarks identified across shape instances have consistent topology.…”
Section: Introductionmentioning
confidence: 99%